PERJANJIAN JUAL BELI ONLINE PENGGUNAAN SHOPEE PAY LATER TINJAUAN HUKUM ISLAM, HUKUM EKONOMI ISLAM DAN KUHPERDATA - Hapsari, Nia Puspita; Ruswanti, Endang; Juwita, Silvia Ratna; Fitria, Annisa (Lex Jurnalica, 2024)
AbstractMany Shopee Pay Later users are disappointed with the policies implemented by Shopee Pay Later, such as fines, delays, etc. The research aims to find out comparative practices between Islamic Law, Islamic economic law, and KHUPerdata in the use of Shopee Pay Later online buying and selling. The methods are: normative juridical and qualitative. Legal research on written regulations is carried out by reviewing library materials or secondary materials. Through normative approaches,e namely: approaches based on key legal entities, examining theories, concepts, legal principles, and legal provisions related to this research. The conclusion shows that concept Islamic law violates the law contrary to provisions of Islamic law, namely: regarding the position of Islamic law is invalid. At the same time, this is no allowed administrative processing fees in calculating the percentage of Qardh funds based on the DSN Fatwa of the Al-Qardh contract No.19/DSNMUI/IV/2001 Civil Code and related regulations that remain in effect.